Mortality in an Early Ontario Community: Belleville 1876–1885 - Sawchuk, Larry; Burke, Stacie (Urban History Review / Revue d'histoire urbaine, 2000)
This study contributes to our understanding of health in late nineteenth-century communities in Ontario and the major factors contributing to the high mortality of the period. The focus of the study is Belleville, Ontario, from 1876 to 1885. Life expectancies at birth in the low forties characterized the community with infant mortality rates in the very high range, 160 per 1000 live-births. Major contributors to the observed pattern of mortality included tuberculosis, weanling diarrhea, and scarlet fever. Significant differences in the likelihood of dying from these three major causes varied by gender and religious affiliation. It is possible that more extended patterns of breast-feeding among Catholics led to lower levels of weanling diarrhea mortality in their infants.